P3.105 Maternal syphilis in british columbia, canada: 2010 to 2016. (8th July 2017) - Wong, J; Arkell, C; Durigon, M; Makaroff, S; Montgomery, C; Morshed, M; Money, D; Schalkwyk, J van; King, A; Gilbert, M; Grennan, T; Ogilvie, G
Abstract : Introduction: From 2010 to 2016, syphilis rates have tripled among women in British Columbia (BC), Canada. We sought to characterise maternal syphilis cases in BC to identify areas to strengthen syphilis prevention programming. Methods: Virtually all syphilis tests in BC are performed at the provincial laboratory. Positive tests are reviewed by centrally-located expert clinicians who diagnose, stage, and recommend treatment. Demographic and treatment information of syphilis cases (primary, secondary, early and late latent) diagnosed in pregnant women (or within 90 days after delivery) from January 2010 to July 2016 were reviewed and descriptive analyses performed. We assessed prenatal syphilis screening based on the prenatal flag on the laboratory requisition and compared against the number of live births reported by BC Vital Statistics. Results: From 2010 to 2015, 2 83 168 syphilis tests were done as part of prenatal testing, compared with 2 64 496 live births. From 2010 to July 2016, there were 45 maternal syphilis cases reported (18 early latent, 27 late latent–of note, syphilis screening by EIA commenced July 2014). The majority of cases (38/45) lived in Greater Vancouver; median age 30 years (range: 20–46). 27, 13, and 3 cases were diagnosed in the first, second, and third trimester, respectively; 2 were diagnosed post-partum. Treatment information was available on 44/45 cases: 42 cases received ≥2 penicillin injections and 2 received doxycycline. Being born outside Canada or having a partner in a developing country was the most common risk factor identified (n=13). One case reported sex trade work, 4 reported having casual sex (>4 partners), and 4 reported substance use. Few cases (6/34) reported ≥2 partners in the last year. Conclusion: Most maternal syphilis cases are diagnosed by first trimester prenatal screening, but a few remain diagnosed post-partum. Increasing efforts to engage early for those born in high syphilis incidence countries (or whose partners remain in such countries) and repeat screening may be areas for focus.